Saliva of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) inhibits classical and alternative complement pathways. Issue 1 (December 2016) - Silva, Naylene; Vale, Vladimir; Franco, Paula; Gontijo, Nelder; Valenzuela, Jesus; Pereira, Marcos; Sant'Anna, Mauricio; Rodrigues, Daniel; Lima, Walter; Fux, Blima; Araujo, Ricardo
Abstract Background Rhipicephalus (Boophilus )microplus is the main ectoparasite affecting livestock worldwide. For a successful parasitism, ticks need to evade several immune responses of their hosts, including the activation of the complement system. In spite of the importance ofR. microplus, previous work only identified one salivary molecule that blocks the complement system. The current study describes complement inhibitory activities induced byR. microplus salivary components and mechanisms elicited by putative salivary proteins on both classical and alternative complement pathways. Results We found thatR. microplus saliva from fully- and partially engorged females was able to inhibit both pathways. Saliva acts strongly at the initial steps of both complement activation pathways. In the classical pathway, the saliva blocked C4 cleavage, and hence, deposition of C4b on the activation surface, suggesting that the inhibition occurs at some point between C1q and C4. In the alternative pathway, saliva acts by binding to initial components of the cascade (C3b and properdin) thereby preventing the C3 convertase formation and reducing C3b production and deposition as well as cleavage of factor B. Saliva has no effect on formation or decay of the C6 to C8 components of the membrane attack complex. Conclusion The saliva ofR. microplus is able to inhibit the early steps of classical and alternative pathways of the complement system. Saliva acts by blocking C4 cleavage and deposition of C4b on the classical pathway activation surface and, in the alternative pathway, saliva bind to initial components of the cascade (C3b and properdin) thereby preventing the C3 convertase formation and the production and deposition of additional C3b.